(untitled) (Research Journal, 2024)
This article attempts to view myself through an auto-ethnographic lens and tries to answer one of the crucial questions - who am I from an academic perspective? The bedrock of this question is the deep realization of the significance of knowing oneself and reflecting on own teaching and researching experiences that can refine and sharpen the teaching profession in general, and own teaching and researching skills in particular. Therefore, I used my nineteen academic articles, four mini-researches, and one large-scale research as major sources of data for this auto-ethnographic study. I wrote them during my two-and-a-half decade-long teaching career. Indeed, they helped me know myself from an academic perspective; and I found that I am a professional teacher, reflective practitioner, critical thinker, classroom researcher, teacher-researcher, action researcher, and an auto-ethnographer who is keenly interested in fostering the research culture as a way of academic life following the essence of the glocalization.